Frente de Aragon. "Autobus en el que unos muchachos de Pina del Ebro trataron a llegar a Osera." Copied from CNT collection
Frente de Aragon. "Autobus en el que unos muchachos de Pina del Ebro trataron a llegar a Osera." Copied from CNT collection.